Salus: Health and salvation in science and in the Church Fathers - Oio, Pablo Damián (Razón y fe, 2023)
The experience of illness and well-being in the human being has given rise to different conceptions about health. With the use of the same term salus, the relationship between the health and the salvation worked by Christ is perceived. For these reasons, in this text, a review of the aspects that, in the scientific field, were highlighted about health and illness is made, also defining health from psychology. Then, biblical texts that speak to us of the healing worked by God in human beings are presented. Finally, the richness of the reflections of the Church Fathers on health and illness, therapy, healing, and salvation is exposed. In this way, the relationship and unity between modern concepts of health and salvation realized by Christ in each person can be discovered.
Keywords: health; illness; salvation; science; psychology; Church Fathers